Biofilm Formation on Bandage Contact Lenses Worn by Patients with the Boston Type 1 Keratoprosthesis: A Pilot Comparison Study of Prophylactic Topical Vancomycin 15 mg/mL and Linezolid 0.2%. (September 2018) - Farooq, Asim V.; Hou, Joshua H.; Jassim, Sarmad; Haq, Zeeshan; Tu, Elmer Y.; de la Cruz, Jose; Cortina, Maria S.
Abstract : Objectives: To determine the rate of biofilm formation on bandage contact lenses worn by patients with the Boston type 1 keratoprosthesis (K-Pro) while on prophylactic topical vancomycin versus linezolid. Methods: Patients wearing a bandage contact lens (BCL) with a K-Pro were eligible for enrollment. After irrigation of the ocular surface with 5% povidone-iodine solution, each patient was placed on either topical vancomycin 15 mg/mL or linezolid 0.2% BID for one month. At the one-month visit, the BCL was collected and stored in fixative solution. Standard photographs were taken of each lens at high magnification using scanning electron microscopy (SEM), which were subsequently analyzed for evidence of biofilm. Results: Nineteen contact lenses were obtained from 12 K-Pro patients at the Illinois Eye and Ear Infirmary. Zero of eight (0%; 95% CI=0 to 37%) contact lenses from patients treated with topical vancomycin, and 1 of 11 (9%; 95% CI=0 to 41%; P -value=1.00) contact lenses from patients treated with topical linezolid were found to have biofilm formation at one month as detected by SEM. None of the patients developed a clinically significant infection while on either prophylactic vancomycin or linezolid during the study period. Conclusions: Overall, the rate of biofilm formation as detected by SEM on the surface of bandage contact lenses was low. These results suggest that vancomycin and linezolid are both relatively effective in reducing biofilm-forming bacterial growth at one month. Accordingly, linezolid may be an effective alternative to vancomycin in patients with allergy or intolerance. However, further investigation is required to develop evidence-based antibiotic prophylaxis regimens.